THE METHOD OF MAKING A DECISION ON BANDWIDTH ALLOCATION OF TELECOMMUNICATION CHANNEL BASED ON LINEAR PROGRAMMING - Kostiantyn O. Polshchykov; Mykola O. Masesov; Yurii M. Zdorenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article proposed a method for making decisions on allocating bandwidth telecommunication channel in the transmission of data flows of different classes. The method is based on the use of linear programming.